Efektifitas Variasi Window Width Terhadap Informasi Anatomi CT Scan Sinus Paranasal Citra Jaringan Lunak Pada Kasus Sinusitis - Tezar Ridho Ramadhani; Siti Masrochah; Ary Kurniawati (Jurnal Imejing Diagnostik (JImeD), 2023)
Background: Selection window width (WW) and window level (WL) must be precise to produce an optimal overview of anatomical information on CT scan paranasal sinuses soft tissue window in case of sinusitis. WW affects controlling contrast resolution. A wide window width will appear the less contrast of image. The aim of the study is to know the difference in anatomical information with variation WW and to know the most optimal WW value for CT scan paranasal sinuses soft tissue window in case of sinusitis.Methods: The research design is a quantitative experimental study, using WW variations (90, 120, 200, 350, 400). Anatomical assessment of osteomeatal unit, agger nasi cell, ethmoid roof, onodi cells, sphenoid sinus, optic nerve, middle turbinate, uncinate process, haller cells, And ethmoidal bulla. The friedman test is used to know a significant difference and the highest value of mean rank to know the most optimal WW value.Results: There is difference in information on each anatomical object with a significance value of 0.05 and there is difference in the total information on anatomical object with a significance value of 0.000 0.05. WW 120 is most optimal to display osteomeatal unit, agger nasi cell, ethmoid roof, onodi cells, middle turbinate, uncinate process, and ethmoidal bulla. WW 90 is most optimal to display sinus sphenoidalis, optic nerve, and haller cells.Conclusions: WW 120 is most optimal to display total anatomical information on CT scan paranasal sinuses soft tissue window in case of sinusitis.